2021
DOI: 10.3389/fpsyt.2021.749379
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mediating Effect of Risk Perception on the Relationship Between Time Perception and Mental Health of College Students During the COVID-19 Epidemic

Abstract: Background: COVID-19 has had a wide impact on the mental health of college students. This study aims to explore the relationship between time perception, risk perception, and the mental health of college students during COVID-19 through a questionnaire survey.Subjects: One thousand two hundred and eighteen college students, 449 male and 769 female, who studied online during the COVID-19 epidemic were selected.Methods: Time Perception Scale, Risk Perception Scale, and SCL-90 were used to investigate the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Offline classes were switched to online learning in dormitories to avoid face-to-face contact between teachers and students and between students, so as to cut down the spread and infection of the pandemic. This situation is likely to adversely affect college students’ mental health and cause them to suffer from anxiety, depression, and insomnia ( 4 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Offline classes were switched to online learning in dormitories to avoid face-to-face contact between teachers and students and between students, so as to cut down the spread and infection of the pandemic. This situation is likely to adversely affect college students’ mental health and cause them to suffer from anxiety, depression, and insomnia ( 4 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…For college students, they have to change their lifestyles and reduce their social activities during the COVID-19 pandemic ( 2 ). In the context of social isolation, the reason for the limitations of their living environment, and the pressure from online learning, they are more likely to suffer from mental health problems ( 3 , 4 ), including anxiety, depression, and insomnia. Zhang et al ( 5 ) reported that the prevalence rates of anxiety and depression among Chinese college students were 10.3 and 25.1% during the COVID-19 pandemic, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature has explored that health risk perception is usually related to tobacco [35], illness [36], and extreme weather [37]. It plays an important role in motivating people to adopt healthy behaviors [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, they are alert and sensitive to health information. Their knowledge, protective behavior, and risk awareness have a significant impact on those around them's risk perception (5,6). Therefore, college students are the key population for epidemic prevention and control, and it is necessary to focus on their risk perception and mental health.…”
Section: Introductionmentioning
confidence: 99%